PENDIDIKAN ISLAM DALAM DINAMIKA GLOBAL - Asnah, Asnah (FORUM PAEDAGOGIK, 2014)
AbstrakEducation of Islam is confessed by its existence in system education of national, it is divided to three things. First, education of Islam as institute, second, education of Islam as subject and third education of Islam as value (value). Education of Islam has to keep abreast of global without losing its idealism. As institute, education of Islam requires to conduct breakthrough preparing capable grad to execute the function, developing and exploiting technology and science at kindliness and reaching the truth of pursuant to Islam values. As subject, it needs integration effort and of interconnection theologies with public sciences. Hereinafter as value education of Islam, it is required to be developed by model of internalization that is formed by superman or with a good quality which remains to be consistent with Islam values.Keywords: Education, Islam and Globalization